PREVALENCE AND CLINICAL CHARACTERISTIC OF MIGRAINE AMONG ADULT POPULATION OF MONGOLIA - Byambasuren, Tsenddorj; Undram , Lkhagvaa; Burmaajav , Badrakh (EurasianUnionScientists, 2020)
Objective: Migraine is the most prevalent public-health problem, affecting people in all countries. Epidemiological data on headache and migraine are not available in Mongolia. Aim of our study was to estimate the prevalence and characteristic of migraine in Mongolia. Methods: We interviewed randomly selected 2043 biologically unrelated adults (aged 18–65 years) in a door to door survey from Ulaanbaatar and four aimags using a pilot-tested, validated, structured HARDSHIP questionnaire. ICHD-II diagnostic criteria were applied. Results: 1-year prevalence of primary headache was 63.9 %, with a female preponderance of 2:1. The age-standardized 1-year prevalence of migraine was 24.2 %, higher among females than males (OR=2.4, 95% CI [1.7-2.6]) and among those with high education (OR=3.0, 95% CI:1.5-5.8]). The estimated prevalence of all headache on ≥15 days/month was 11.2 % (that of pMOH was about 70%). Conclusion: Prevalence of primary headache was 63.9% with migraine having 24.2%. Female gender, education level and family history were associated with Migraine.